Prevention of occupational injuries and accidents: A social capital perspective. Issue 4 (13th May 2020) - Hafeez, Hira; Abdullah, Muhammad Ibrahim; Riaz, Amir; Shafique, Imran
Abstract: Prior research has consistently established the pragmatic nature of literature regarding occupational injuries and accidental happenings faced by nursing professionals. However, current realities require a subjective approach to identify preventative measures that could influence occupational health and safety in healthcare sectors. A qualitative design followed a descriptive approach to assess unbiased opinions towards occupational obstructions that lead to accidental happenings. This study used the social capital framework in particular as a support resource to eliminate its detrimental effects on nurse's capacity to serve their patients. The findings extended the fundamental understanding of social capital from social ties to workplace and personal ties as potential mechanisms of support. Healthcare organizations need to redefine their control policies to provide the ultimate support to their care agents. A social capital model offers nursing practitioners and nursing managers an approach for building evidence‐based policies with implications for nurse's safety, education and training.